The Effect of Corporate Sustainability Practices on Tax Avoidance: Evidence from Indonesia - Dalimunthe, Esmil Saleh; Fachrudin, Khaira Amalia; Nasution, Fahmi Natigor (Jurnal Manajemen Stratejik dan Simulasi Bisnis, 2024)
Environmental, Social, and Governance (ESG) factors are currently receiving significant attention from investors and company management. This study aims to analyze the relationship between ESG performance and tax avoidance among companies in Indonesia. The research utilizes financial statement data from non-financial sector companies listed on the Indonesia Stock Exchange for 2019–2023. Financial data and ESG scores were sourced from the LSEG Refinitiv database. Data analysis was conducted using a quantitative approach with the EViews 13 software. The results indicate a significant negative relationship between ESG scores and tax avoidance. This finding suggests that companies with strong ESG performance are less likely to engage in tax avoidance practices. These results align with agency and stakeholder theories, which propose that companies with effective governance are less inclined to participate in tax avoidance activities.